Effect of thermal annealing on the structure of LiCoO2 powders prepared by co-precipitation method. (December 2021) - Khejonrak, Awadol; Chanlek, Narong; Sukkha, Usa; Triamnak, Narit; Chirawatkul, Prae; Kidkhunthod, Pinit; Suttapun, Manoon; Vittayakorn, Naratip; Manyum, Prapan; Rujirawat, Saroj; Songsiriritthigul, Prayoon; Yimnirun, Rattikorn
Abstract: Lithium cobalt oxide (LiCoO2 ) powder was prepared by co-precipitation method and annealed at different temperatures of between 300 and 700 °C. The effect of annealing temperature and effect washing process with deionized water on the crystal structures of the prepared LiCoO2 powders were thoroughly studied by Synchrotron powder X-Ray Diffraction (Syn-XRD), X-ray Absorption Spectroscopy (XAS), Dispersive Raman Microscopy (Raman) techniques. The change in chemical composition as a function of annealing temperature was also investigated by X-ray Photoelectron Spectroscopy (XPS) technique. The crystal structural results identified the phase evolution of the prepared LiCoO2 powders upon heat treatment. The formation of HT-LiCoO2 phase was observed at annealing temperature as low as 300 °C. Highlights: Structure of LiCoO2 powder was studied by Synchrotron XRD and XAS techniques. Formation of HT-LiCoO2 phase was observed at annealing temperature of 300 °C. Washing process affects surface chemical composition of LiCoO2 powder.